OWASP A03 Injection vulnerability in Web Application Development - Andy, Chieng Ging Wei (Universiti Malaysia Sarawak (UNIMAS), 2023)
In this information technologies era, more and more hacker appeared to attack the vulnerable web application on the internet. As a web developer to be, the junior web developer has to be equipped with knowledge and be prepared to handle the common vulnerability in web application. To accommodate with this goal, this project is being proposed and developed to teach the web developer on the fundamental about Open Web Application Security Project (OWASP) Top 10, focusing on OWASP Top 10 A03 - Injection vulnerability. OWASP A03 Injection vulnerability is one of the most common vulnerabilities can be found in the web application. In this web application, web developer will be well-educated on the vulnerability as well as the defencing ways to enhance the security of the web application developed that can defenceagainst this vulnerability. Besides, several research paper and the existing application related will be reviewed as a resource of requirement gathering which helps in designing on the functionality and features of web application complied with OWASP A03 Injection vulnerability. Other than that, the development of the web application will be documented. Besides, the result on testing on the web application will be analysed in this report. From the positive result gained from testers involved in both laboratory usability testing and usability testing using system usability scale, it is believed that this project can help to increase understanding of the web developer on the OWASP A03 vulnerability.